Analysis of Phytoconstiuents and Cytotoxic Activities of Different Parts of Ocimum sanctum - Joshi, Sushika; Karna, Anish Kumar (International Journal of Applied Sciences and Biotechnology, 2013)
Phytochemical screening of extracts of Ocimum Sanctum revealed the presence of fatty acids, steroids, triterpenoid, phenolic compound, flavonoid, glycoside, quinines, and carotenoids. β-sitosterol and Ursolic acid were isolated from leaves of the plant by using column chromatography and identification of these compounds were performed with the help of melting points, Co-TLC and spectroscopic techniques such as IR, 1HNMR and 13 CMR. GC-MS of hexane fraction showed presence of pentanal, sotolone, hexane-3-one, hexane-2-ol, caryphyllene, benzene 1,2 di-carbolylic acids, isoeugenol, cavracrol and eugenol compounds. The brine shrimp bio assay showed LC50 value 213.7, 97.72 and 21.87 for hexane, ethyl acetate and methanol extracts of leaves respectively, where as LC50 value 169.84, 141.25 and 151.35 for hexane, ethyl acetate and methanol extracts of stem respectively. All extracts are pharmacologically active. DOI: http://dx.doi.org/10.3126/ijasbt.v1i3.8609 Int J Appl Sci Biotechnol, Vol. 1(3) 2013 : 137-144